CORRELATIONS BETWEEN THE DIMENSIONS OF JOB SATISFACTION AND LEADER-MEMBAR EXCHANGE IN THE TOURISM AND PUBLIC SECTOR - Vanić, Tatjana; Nedeljković Knežević, Milena (Poslovna ekonomija, 2017)
Today, in organizations, one of the most important guidelines is to achieve management efficiency and the ability to influence the employees to carry out the requirements and decisions and thereby fulfill their own goals. One of the prerequisites for achieving the above-mentioned organizational and individual goals is a high quality of relationships between leaders and followers, to enable employees  to be efficient, successful  and  happy at work. In the tourism sector most frequent forms of organization is the teamwork with the leader of the team, with a high degree of flexibility in decision-making. In the public sector  the “space” for a flexible approach to decision-making process is considerably reduced, because the state, in accordance with its laws, significantly influence the process. Since job satisfaction has many important implications (such as, for example,  the quality of work performances), we investigated the correlations between  the dimensions of job satisfaction and leader-member exchange quality.
Keywords: JOB SATISFACTION; TOURISM; QUALITY; leader; Job Satisfaction; EMPLOYEES